Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# Find the value of $38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8)$

Last updated date: 15th Sep 2024
Total views: 399.9k
Views today: 7.99k
Verified
399.9k+ views
Hint: In this question, we have to solve the given numerical expression. The numerical expression comprises the arithmetic operations like addition, subtraction and multiplication. We will start solving the question by writing $- ( - 25)$ as $- 1( - 25)$ , that is equal to the product of -1 and -25. We know that the product of two negative numbers is equal to a positive number, so the answer obtained will be a positive value. Now the sign between 38 and the number obtained will be a plus sign, so we will add the number obtained with 38. The value obtained will be positive as two positive values are added to each other. Following a similar approach, we will simplify all the numbers in the given expression and thus get the correct answer by performing the given arithmetic operations.

Complete step-by-step solution:
We have to find the value of $38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8)$
We know that $- ( - a) = a$ so $- ( - 25) = 25$ and $- ( - 8) = 8$
We also know that $+ ( - a) = - a$ so $+ ( - 15) = - 15$
So, we get –
$38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8) = 38 + 25 - 58 - 15 - 23 + 8$
$38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8) = 63 - 58 - 15 - 23 + 8$
$38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8) = 5 - 15 - 23 + 8$
$38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8) = - 10 - 23 + 8$
Now, $- a - b = - (a + b)$ so –
$38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8) = - 33 + 8 \\ \Rightarrow 38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8) = - 25 \\$
Hence, the value of $38 - ( - 25) - 58 + ( - 15) - 23 - ( - 8)$ is $-25$.
Note: Numbers are of two types namely real numbers and imaginary numbers, real numbers are the numbers that can be shown on a number line. The numbers on the left side of the zero are negative and the numbers on the right side are positive. While multiplying two numbers, we multiply the signs of the numbers along with them. The signs are multiplied as (+)(+)=(+), (+)(-)=(-), (-)(+)=(-) and (-)(-)=(-) that’s why $a - ( - b) = a + b$.